Sinai Trafficking: Origin and Definition of a New Form of Human Trafficking - Reisen, Mirjam van (Social Inclusion, 2015)
The phenomenon that is coined “Sinai Trafficking” started in 2009 in the Sinai desert. It involves the abduction, extortion, sale, torture, sexual violation and killing of men, women and children. Migrants, of whom the vast majority are from Eritrean descent, are abducted and brought to the Sinai desert, where they are sold and resold, extorted for very high ransoms collected by mobile phone, while being brutally and “functionally” tortured to support the extortion. Many of them die in Sinai. Over the last five years broadcasting stations, human rights organisations and academics have reported on the practices in the Sinai and some of these reports have resulted in some confusion on the modus operandi. Based on empirical research by the authors and the analysis of data gathered in more than 200 recorded interviews with Sinai hostages and survivors on the practices, this article provides a definition of Sinai Trafficking. It argues that the term Sinai Trafficking can be used to differentiate a particular new set of criminal practices that have first been reported in the Sinai Peninsula. The article further examines how the new phenomenon of Sinai Trafficking can be framed into the legal human trafficking definition. The interconnectedness of Sinai Trafficking with slavery, torture, ransom collection, extortion, sexual violence and other severe crimes is presented to substantiate the use of the trafficking framework. The plight of Sinai survivors in Israel and Egypt is explained to illustrate the cyclical process of the trafficking practices especially endured by Eritreans, introduced as the Human Trafficking Cycle. The article concludes by setting out areas for further research.